Placing rehabilitation at the core of assertive community treatment. (February 2021) - Siskind, Dan; Dark, Frances; Carney, Kylie; Gore-Jones, Victoria; Kar Ray, Manaan; Steginga, Anne; Suetani, Shuichi; Kisely, Stephen
Objectives: Assertive community treatment (ACT) teams are increasingly being adapted to suit the needs of consumers who have never experienced long-term institutional care yet struggle to retain community tenure and quality of life due to residual functional disabilities associated with severe mental illness. Support needs can be provided by the growing disability support sector but recovery-orientated rehabilitation services delivered by specialist rehabilitation clinicians are also required. The Mobile Intensive Rehabilitation Team (MIRT) within the Metro South Addiction and Mental Health Service has adapted the ACT model to deliver assertive outreach that aims to work collaboratively with the person and their chosen supports to improve their function and their sense of self-efficacy in illness self-management. We described the characteristics of the consumers referred to MIRT over a 20-month time period, and reported on on their discharge location. Conclusion: After two years with MIRT, half the participants were discharged out of case-management. Being on clozapine was a barrier to discharge from case-management despite functional improvement. Psychiatric hospitalisations predicted longer duration working with MIRT.